PENGARUH KONSENTRASI AMMONIUM SULFAT ((NH4)2SO4) OPTIMASI JAMUR JERAMI PADI ILS (ISOLAT LOKAL SINGARAJA) UNTUK BIODEGRADASI ZAT WARNA AZO JENIS REMAZOL RED - Sukarta, I Nyoman; Sumahandriyani, Putu (Jurnal Kimia (Journal of Chemistry); Vol. 7, No. 1 Januari 2013DO - 10.24843/JCHEM.2013.v07.i01.p12)
This study aims to determine the concentration, contact time, and the optimum pH required by the ILS rice straw mushrooms to degrade azo dyes remazol red type. Subject in this study is ILS rice straware mushroom which is obtained from existing fields in Temukus Village, Banjar District, Buleleng Regency. The objecs are the concentration, contact time, and the optimum pH required by the ILS rice straw mushroom to degrade textile dyes remazol red type. Stage of data collection starts from the preliminary test biodegradability of dyes, mold growing on PDA medium (potato dextrosa agar) and liquid Czapex, qualitative test of lignolitic enzyme, and dye biodegradation test on the variation of environmental conditions. The concentrations of remazol red dye before and after degraded by the ILS rice straw mushroom was measured by using a Hach spectrophotometer. The results showed that the degradation of azo dyes type remazol red RB using the ILS rice straw mushroom was optimum at color concentration of 30 ppm, contact time of 10 days, and pH 5 with the efficiency of each of 57,77; 71,13; and 50,88%.
Keywords: ILS rice straw mushroom, biodegradation, remazol red, and the lignolitic enzyme